CONTROLE QUÃMICO DA MANCHA ZONADA (Leandria momordicae) EM PEPINO - Lopes, Maria Elizabete Barretto de M.; Sinigaglia, Celso; Azevedo Filho, Joaquim A. (REVISTA DE AGRICULTURA, 2015)
CONTROLE QUÃMICO DA MANCHA ZONADA (Leandria momordicae) EM PEPINO